ANALISIS RASIO SOLVABILITAS DAN RASIO PROFITABILITAS PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 - 2016 - Ivana Nina Esterlin Barus 3, Ade Molina Mardiana 2 (EKONOMIA, 2021)
Basis used in analyzing financial statements are financial management that focuses on solvency ratio and the ratio on profitability. The hypothesis of this research is the debt to total asset ratio at the firm, which is increasing and decreasing and return on asset ratio are increased and decreased. Analysis tools are used to find out the ratio of solvency ratio analysis and profitability at retail companies listed on the Indonesia stock exchange period using the formula 2014-2016 solvency ratio (debt to total asset ratio) and the formula the ratio of profitability (return on asset ratio).Based on the results of the analysis of the debt to total asset of tatal known retail companies a 62,5% increment on debt in the period 2014-2015, and wxperinced a 60% debt increment period 2015-2016.Â And based on the results of the analysis of the return on assets of the companyâ€™s retail profits decreased by 81,25% in the period 2014-2015. And increase of 56,25% in the periode 2015-2016.